Social media as a student response system : new evidence on learning impact - Liu, Chelsea (Research in learning technology, 2018)
The ubiquitousness of social media renders it a potentially powerful tool in higher education. This study explores the use of Twitter as a tool to enhance active learning and improve feedback during large-sized lectures. Students in a final-year undergraduate accounting course at an Australian university engaged in Twitter-based synchronous activities, including answering in-lecture quizzes and posting questions. This study explores two key questions: (1) 'what encourages students to actively utilise social media in their learning process?' and (2) 'what pedagogical advantages are offered by social media in enhancing students' learning experiences?' Results of a student survey administered at the end of the course show that (1) students are more likely to participate in in-lecture Twitter activities if they are familiar with the technology, (2) Twitter activities encourage students to participate in active learning, (3) Twitter provides a platform enabling two-way student-instructor communication and (4) students find Twitter activities helpful regardless of whether they attend the lecture in real time or view online lecture recordings. These findings deepen our understanding of the pedagogical benefits of using Twitter as a student response system, which will assist educators to better harness the power of social media in the learning-teaching process. [Author abstract]